Targeting MicroRNA-21 Suppresses Gastric Cancer Cell Proliferation and Migration via PTEN/Akt Signaling Axis - Hao Zhou (Cell Transplantation, 2019)
MicroRNA plays a pivotal role in various human cancers, especially in human gastric cancer. In the present study, we evaluated the effect of microRNA-21 (miR-21) on the gastric cancer cell proliferation, migration, apoptosis and the related signaling cascades. Here, we showed that down-regulation of miR-21 markedly reduced gastric cancer cell proliferation (AGS and NCI-N87 cells) in a time dependent manner. Moreover, our findings revealed that silencing miR-21 dramatically blocked gastric cancer cell migration and movement, which might be related to down-regulation of vimentin expression. We also found that down-regulation of miR-21 promoted cell apoptosis and repressed cell cycle progression. Further investigation showed that down-regulation of miR-21 significantly increased phosphatase and tensin homolog (PTEN) protein expression level, but not transcription level (mRNA level), which in turn decreased Akt phosphorylation at Thr308 and Ser473. Collectively, our results uncover that miR-21 targets PTEN/Akt signaling pathway and regulates cell proliferation, migration and apoptosis in human gastric cancer cells. Our findings may provide a therapeutic target for treatment of human gastric cancer.